HASSAN HANAFI'S QURANIC HERMENEUTICS: ANALYSIS OF THE INTERPRETATION OF THE TERMS AL-AR? AND AL-M?L - Taufiqurrahman, Taufiqurrahman (el-Umdah, 2024)
This article questions the extent to which Hassan Hanafi's phenomenological hermeneutical ideas can be applied in understanding the text of the Quran. The research adopts a literature approach in critically examining the hermeneutics of the Quran by Hassan Hanafi, with a focus on the interpretation application regarding land (al-ar?) and property (al-m?l). The primary data sources primarily come from several of Hasan Hanafi's works. The research findings indicate that Hassan Hanafi's phenomenological hermeneutics is fundamentally based on the maudhu'i interpretation method. His interpretations do not apply the principle of hermeneutics in the sense of verstehen, where the interpreter is subjective and intervenes in the meaning of the text, but rather erklaren, by objectively explaining the text. This can be seen in the understanding of the terms al-ar? and al-m?l, where their interpretations are obtained from the sound of the text or a series of scattered texts in the Quran. Regarding the phenomenology he uses as an approach, it is evident that he takes natural and social phenomena as an explanation of the meaning of the text. This is certainly different from Fazlurrahman, Arkoun, Nasr Hamid Abu Zaid, who elaborate and seem to drift in the vortex of Western thought.